Evaluation of Processing Methods to Control the Growth of Lactobacillus kunkeei, a Micro-organism Implicated in Sluggish Alcoholic Fermentations of Grape Musts - Edwards, C.G.; Haag, K.M.; Semon, M.J.; Rodriguez, A.V.; Mills, J.M. (South African Journal of Enology and Viticulture, 2017)
Processing strategies that could be used to control the growth of the spoilage bacterium Lactobacillus kunkeei during vinification were evaluated.  These strategies included the use of 802, low temperatures, and adjustment of must pH. On the one hand, Lactobacillus kunkeei was sensitive to S02 in that growth was not observed at concentrations greater than 0,1 mg/L molecular 802• On the other hand, the organism remained viable at 5° and 10°C for up to 10 days in a synthetic medium. Regarding low pH, the organism did not grow well in a synthetic medium at less than pH 3,5. Thus Lactobacillus kunkeei was inoculated into fermenting Chardonnay musts adjusted to pH 3,16; 3,50 and 3,80. Although a decrease in must pH resulted in less growth of Lactobacillus kunkeei, the bacterium achieved populations in excess of 108 CFU/mL and all alcoholic fermentations were slowed. Thus, S02 remains the best method for winemakers to control growth of this spoilage bacterium.